Advanced nitrogen removal from real municipal wastewater by multiple coupling nitritation, denitritation and endogenous denitritation with anammox in a single suspended sludge bioreactor. (1st August 2022) - Kao, Chengkun; Li, Jianwei; Gao, Ruitao; Li, Wenyu; Li, Xiyao; Zhang, Qiong; Peng, Yongzhen
Highlights: Multiple coupling PN, PD and EPD with anammox was realized in a suspended sludge SBR. Superior N-removal efficiency of 94% was achieved without external carbon source. Anammox contributed 78% to TIN removal with 5 h aeration times (DO=0.5–0.8 mg/L). Anammox activity and abundance increased during the PNA-(E)PDA process. PNA-(E)PDA provides a novel option on mainstream municipal wastewater treatment. Abstract: Achieving advanced nitrogen removal based on anammox for treating mainstream municipal wastewater in a single suspended sludge bioreactor is a challenging research topic. In this study, multiple coupling nitritation, denitritation and endogenous denitritation with anammox (PNA-(E)PDA) was simultaneously achieved in a 10 L step-feed bioreactor, which enhanced stable nitrogen removal. After 223 days of operation, the total nitrogen concentrations of the influent and effluent were 70.7 ± 6.1 and 4.3 ± 1.8 mg/L, respectively, when treating municipal wastewater even at C/N ratio of 2.24 with only 5 h of aerobic time (DO: 0.5–0.8 mg/L). After the evolution of nitritation/anammox to PNA-(E)PDA, the contribution of anammox to nitrogen removal increased to 78.6% and the anammox activity increased from 4.3 ± 0.2 to 15.2 ± 0.7 mg NH4 + -N/gVSS/d. qPCR results showed that the abundance of anammox bacteria increased from 4.1 × 10 9 to 4.5 × 10 10 copies/ (g VSS). High-throughput sequencing further revealed that the relative abundance of Candidatus Brocadia, the dominant anammox genus, increased from 0.09 to 0.46%. Based on the strong competitiveness of anammox on nitrite, this novel PNA-(E)PDA process provides a potential strategy for enriching anammox bacteria in municipal wastewater treatment plants. Graphical abstract: Image, graphical abstract